TEACHER IMPACT ON THE LEARNING PROCESS - Ismoilova Diloraxon Alisherovna; Abdukarimova Mohira Yusupjonovna; Gaforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The role of teacher in the learning process is crucial as they have a direct impact on the students academic and personal development .This article explores the various ways .in which teachers influence the learning process including their teaching style, classroom management,and ability to motivate and engage students . The article also discusses the importance of building positive teacher – student relationships and the impact of teacher expactations on student performance. Additionally, the article highlights the significance of ongoing professional development for teachers to enhance their effectiveness in the classroom. Overall , the article emphasizes the significant impact that teachers have on shaping the learning experience and outcomes of their students.